The Effect of Training, Work Skills, and Independent Learning on Performance of Gig Workers at BALATKOP UKM Jawa Tegah - Yunita Sinta Amanda; Sungkowo Edy Mulyono (International Journal of Studies in International Education, 2026)
The competitiveness of gig workers in the digital economy era raises issues such as competency gaps with market needs and instability in the quality of gig workers' work. This study explains the influence of training, work skills, and independent learning on the performance of gig workers who participate in training programs at the Central Java Province Cooperative and SME Training Center. Therefore, this study aims to examine the influence of each variable partially and simultaneously. This study uses a quantitative approach by distributing questionnaires to the entire population or using a saturated sample of 50 gig workers participating in training at BALATKOP UKM. The data was obtained using a Likert scale questionnaire instrument compiled based on the operational definitions of the variables and analyzed using multiple linear regression analysis to test the influence of training (X2), work skills (X2), and independence (X3) on performance (Y). The results of the study show that training, job skills, and independent learning each have a positive and significant effect on gig worker performance, and simultaneously, these three variables have a 66.5% effect on performance. This synthesis of findings confirms that gig worker performance is not only determined by the quality of training programs and technical skill mastery, but also by the ability to manage the learning process independently. Therefore, the conclusion is that the development of training programs at BALATKOP UKM needs to be designed in an integrated manner to simultaneously strengthen training, work skills, and independent learning as a strategy for improving the sustainable performance of gig workers.